Antiferromagnetic Cavity Magnon Polaritons in Collinear and Canted Phases of Hematite - Boventer, I.; Simensen, H. T.; Brekke, B.; Weides, Martin; Anane, A.; Klaeui, M.; Brataas, A.; Lebrun, R. (Physical Review Applied, 2023)
Cavity spintronics explores light-matter interactions at the interface between spintronic and quantum phenomena. Until now, studies have focused on the hybridization between magnons in ferromagnets and cavity photons. Here, we realize antiferromagnetic cavity magnon polaritons. Hybridization arises from the interaction of the collective spin motion in single hematite crystals (α-Fe2O3) and the microwave field of integrated cavities operating between 18 and 45 GHz. We show theoretically and experimentally that the photon-magnon coupling in the collinear phase is mediated by the dynamic Néel vector and the weak magnetic moment in the canted phase by measuring across the Morin transition. We show that the coupling strength, g , scales with the anisotropy field in the collinear phase and with the Dzyaloshinskii-Moriya field in the canted phase. We reach the strong-coupling regime in both canted (cooperativity C > 70 for selected modes at 300 K) and noncollinear phases (C > 4 at 150 K), and thus, towards coherent information-exchange-harnessing antiferromagnetic cavity magnon polaritons. These results provide evidence for a generic strategy to achieve cavity magnon polaritons in antiferromagnets for different symmetries, opening the field of cavity spintronics to antiferromagnetic materials.
CRIS-Team Scopus Importer:2023-03-27